GEOCHEMICAL STUDY OF RARE EARTH ELEMENTS DISTRIBUTION IN ACID MINE DRAINAGE AND OVERBURDEN OF COAL MINE (CASE STUDY: PT BUKIT ASAM) - Badhurahman, Abie
Acid mine drainage is one of main environmental impact from mining activities all over the world: from early stage of exploration, exploitation and mine closure. Acid mine drainage is yielded from oxidation reaction of pyrite in saturated condition and charactized by elevated acidity, suphate and dissolved iron. Acid mine drainage can leach overburden which in turn elevating dissolved metals, including rare earth elements (REE). REE is used widely in geochemical analysis of rock-water interaction thus can be used as an indicator of water pollution by acid mine drainage. In the other hand, acid mine drainage can be a source of REE. Acid mine drainage from PT Bukit Asam are geochemically characterized as unique, with elevated dissolved iron and manganese and indication of REE-enrichment. This study aims as an eary stage of REE occurrence and characterization in acid mine drainage and overburden. This study is conducted by using 11 water samples and 24 solid samples of overburden from all area of PT Bukit Asam. Geochemical characterization of those two types of samples shown variability. Nevertheless, both type of samples show medium REE enrichment and enrichment of following elements: La, Ce, Pr, Nd, Sm, Gd, and Dy Generally, enrichment of REE in acid mine dranage are controlled by source of REE in overburden, acid mine drainage producing characterization of overburden as source of acidity which in turns control leaching proccess of REE from source rock and electrochemical characteristic of mine water.